1980
DOI: 10.1073/pnas.77.5.2740
|View full text |Cite
|
Sign up to set email alerts
|

Induction of differentiation of murine erythroleukemia cells by aminonucleoside of puromycin and inhibition of this induction by purines and purine derivatives.

Abstract: The effect of the aminonucleoside of puromycin (AMS) on Friend erythroleukemia cells in culture was investigated, because purines and purine analogues are known to act as inducers of differentiation. After treatment with 20-30 psM AMS for 4 days, the cultures contained between 80 and 90% benzidine-positive cells. Stimulation of hemoglobin synthesis was dose and time dependent. Inosine had no stimulatory activity; however, when it was added to the medium together with AMS, erythroid differentiation was almost c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…This possibility is supported by studies with kinase-deficient mutants that provide evidence for a link between the formation of cytotoxic analog nucleotides and the induction process. Thus, the differentiation inducing ability of xylosyladenine in the presence of an inhibitor of adenosine deaminase is abolished in an adenosine kinase-deficient clone of the Friend erythroleukemia (Lacour et al, 1980). Similarly, bromodeoxyuridine, a moderately effective initiator of the maturation of HL-60 cells, is unable to induce differentiation in a thymidine kinase deficient clone of this tumor (Koeffler et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is supported by studies with kinase-deficient mutants that provide evidence for a link between the formation of cytotoxic analog nucleotides and the induction process. Thus, the differentiation inducing ability of xylosyladenine in the presence of an inhibitor of adenosine deaminase is abolished in an adenosine kinase-deficient clone of the Friend erythroleukemia (Lacour et al, 1980). Similarly, bromodeoxyuridine, a moderately effective initiator of the maturation of HL-60 cells, is unable to induce differentiation in a thymidine kinase deficient clone of this tumor (Koeffler et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of purine and pyrimidine analogs have been shown to be inducers of differentiation in both the Friend (Ebert et al, 1976) and HL-60 (Bodner et al, 1981) leukemias. Some of the active inducers include the aminonucleoside of puromycin (Lacour et al, 1980), 5-bromo-2'-deoxyuridine (Koeffler et al, 19831, 3-deazauridine, pyrazofurin, virazole (Bodner et al, 1981) and xylosyladenine (Garrett and Kredich, 1981). The concentration of these antimetabolites required to initiate maturation is exceedingly close to the level required to produce cytotoxicity, implying that the metabolic actions involved in the production of cytotoxicity and differentiation may be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were performed to determine whether PIA also inhibited induction of MEL differentiation by agents such as HMBA (Reuben et al, 1976), butyric acid , diazepam (Clarke and Ryan, 1980;Wang et al, 19841, hypoxanthine (Gusella and Housman, 1976), and the aminonucleoside analog of puromycin (AMS) (Lacour et al, 1980). The effects of PIA were dependent upon the inducer (Table 3).…”
Section: Resultsmentioning
confidence: 90%
“…Purines have been shown to induce and inhibit induction of differentiation in Friend erythroleukemia cells (25). Conjugation of nucleosides to IgG showed that guanosine was dominant, determining either tolerization or immunization, depending on the experimental protocol (26).…”
Section: Resultsmentioning
confidence: 99%